El Delito de Rebelión y su Impacto en la Protección del Derecho Constitucional a la Resistencia en el Ordenamiento Jurídico Ecuatoriano - González Salinas, Neri Fernando (2024)
In the context of the Ecuadorian legal system, the delicate balance between the right to resistance and the prevention of the crime of rebellion raises fundamental questions about how to guarantee the legitimate exercise of citizen rights while maintaining stability and constitutional order. The analysis of this topic involves exploring how the crime of rebellion is defined, regulated and applied, and how this regulation can influence the protection of the constitutional right to peaceful resistance. Ecuador, like other countries, recognizes the right to resistance as an inherent component of popular sovereignty and citizen participation. The 2008 Constitution establishes in its Article 98 that people have the right to peaceful resistance and conscientious objection as legitimate forms of exercise of their rights. This recognition reflects the democratic value of allowing citizens to express their disagreement with government policies and practices. The crime of rebellion, on the other hand, is conceived as the performance of violent or insurrectionary acts with the intention of overthrowing the established government or altering the constitutional order. This definition implies the use of force and violence as means for political change, which can lead to situations of instability and conflict. The precise delimitation between peaceful resistance and violent rebellion is crucial to understand how this regulation is interpreted and applied. The Ecuadorian legal system faces the challenge of maintaining a balance between the protection of the constitutional order and the promotion of citizen participation. The proportionality of the government's response to actions of resistance and the degree of violence involved are key elements in determining whether an action crosses the line into rebellion. It is essential to prevent the regulation of the crime of rebellion from being used as a tool to silence legitimate criticism and limit freedom of expression. Judicial interpretation plays a fundamental role in defining the limits between resistance and rebellion. Judicial decisions must carefully consider the intent, context, and means used in resistance actions. An interpretation that is equitable and based on democratic principles can help to ensure that both individual rights and the stability of the State are protected.